Information Structure and Interfaces - Jimenez-Fernandez, Angel (IBERIA: An International Journal of Theoretical Linguistics, 2010)
Information structure has been extensively investigated throughout the history of linguistics. From different perspectives and using different terminology, it is generally assumed that information structure includes the notions of topic and focus. The description of information structure in generative grammar can be traced back to Chomsky (1972) and Jackendoff (1972). Within the generative framework, there has been a continuous debate about the impact of these discourse-linked functions upon syntax. A purely syntactic approach to information structure is unconceivable due to the fact that topic and focus have specific semantic and prosodic properties, though subject to cross-linguistic variation.